THE FEATURES OF DEVELOPMENT OF THE PAYMENT CARD MARKET IN UKRAINE - Bilyi , M.M. (The actual problems of regional economy development, 2019)
The article analyzes the current state and major current trends in the development of the payment card market in Ukraine. The domestic professional literature reflects some aspects of these issues, in particular, the role and place of payment systems in the modern world, in socio-economic systems with a market economy. However, issues regarding the development of the payment card market in Ukraine remain poorly understood. There is a need for research that would comprehensively cover the activities of all market entities, including payment institutions, banks, merchants, and cardholders. The purpose of the article is to find out the state and trends of further development, as well as to develop on this basis directions for reforming the payment card market as a component of Ukraine's national payment space. Today, the domestic payment card market is one of the segments of the banking services market, which shows one of the highest rates of development. It is noted that in the conditions of improving the quality of service delivery and lower tariffs for payment card servicing, the payment card market in Ukraine has considerable potential for further development, not only on a national scale, but in case of entering the world level. The key factor in this situation is, first and foremost, the high level of competition, which causes market participants to constantly introduce new, quality banking products. According to world standards, the current state of the payment card market in Ukraine has all the features of an emerging market. In view of this, the article highlights the main characteristics inherent in the highly developed payment card market in the light of global experience. The main trends in the development of the payment card market in Ukraine are analyzed on the basis of a number of absolute and relative indicators of the market during 2010-2019, outlined the main measures that will contribute to the further development of the specified sector of banking services in our country.